2012
DOI: 10.1371/journal.pone.0033348
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1–D2 Receptor Heteromer in Dual Phenotype GABA/Glutamate-Coexpressing Striatal Medium Spiny Neurons: Regulation of BDNF, GAD67 and VGLUT1/2

Abstract: In basal ganglia a significant subset of GABAergic medium spiny neurons (MSNs) coexpress D1 and D2 receptors (D1R and D2R) along with the neuropeptides dynorphin (DYN) and enkephalin (ENK). These coexpressing neurons have been recently shown to have a region-specific distribution throughout the mesolimbic and basal ganglia circuits. While the functional relevance of these MSNs remains relatively unexplored, they have been shown to exhibit the unique property of expressing the dopamine D1–D2 receptor heteromer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 47 publications
(66 reference statements)
5
73
1
2
Order By: Relevance
“…It has also been proposed that D 1 -D 2 heteromer activation via SKF83959 in vivo and in vitro results in increased Ca 21 /calmodulin-dependent protein kinase IIa levels in the striatum and nucleus accumbens, further resulting in enhanced brain-derived neurotrophic factor expression and increased neuronal maturation and differentiation (Rashid et al, 2007a;Hasbi et al, 2009;Ng et al, 2010;Perreault et al, 2012b). Given that our experiments indicated that SKF83959 could not induce D 1 -D 2 heteromer-selective calcium mobilization in a controlled cell environment, we conducted a single-point competition-binding screen against an array of 43 GPCRs and additional signaling proteins (Supplemental Table 1; Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been proposed that D 1 -D 2 heteromer activation via SKF83959 in vivo and in vitro results in increased Ca 21 /calmodulin-dependent protein kinase IIa levels in the striatum and nucleus accumbens, further resulting in enhanced brain-derived neurotrophic factor expression and increased neuronal maturation and differentiation (Rashid et al, 2007a;Hasbi et al, 2009;Ng et al, 2010;Perreault et al, 2012b). Given that our experiments indicated that SKF83959 could not induce D 1 -D 2 heteromer-selective calcium mobilization in a controlled cell environment, we conducted a single-point competition-binding screen against an array of 43 GPCRs and additional signaling proteins (Supplemental Table 1; Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have used this finding to interpret the results of systemic SKF83959 injections in mice, which resulted in increased Ca 21 /calmodulindependent protein kinase IIa phosphorylation and increased brain-derived neurotrophic factor expression in striatal neurons (Hasbi et al, 2009;Ng et al, 2010). It was also shown that expression of glutamate decarboxylase-67 and the vesicular glutamate transporters 1 and 2 in striatal neurons, when injected into rats, was altered by SKF83959 (Perreault et al, 2012b), which, again, was interpreted to be due to selective D 1 -D 2 heteromer activation.…”
Section: Introductionmentioning
confidence: 97%
“…Coexpression of D1R and D2R within a medium spiny neuron (MSN) does not necessarily indicate heteromerization per se, but the D1-D2 receptor-receptor distance determined to be o100 Å documented by the FRET analyses is indicative of heteromer formation. Specifically, the D1-D2 heteromer was found to be selectively expressed in MSNs with a unique phenotype, in that these neurons also expressed both dynorphin (DYN) and enkephalin (ENK) (Perreault et al, 2010), as well as GABA and glutamate (Perreault et al, 2012), and to have representation along both the direct striatonigral and indirect striatopallidal pathways (Perreault et al, 2010). For example, while a relatively low number of D1R-containing MSNs expressed the D2R (B6%) in caudate putamen (CP), higher coexpression levels were evident in ventral pallidum and entopeduncular nucleus, with the highest levels documented in the nucleus accumbens (NAc) shell (B17-34%) and globus pallidus (B60%) (Bertran-Gonzalez et al, 2008;Perreault et al, 2010).…”
Section: The Dopamine D1-d2 Receptor Heteromermentioning
confidence: 99%
“…The D1-D2 heteromer has been shown to exhibit pharmacological and cell signaling properties distinct from its constituent receptors (Hasbi et al, 2009;Lee et al, 2004;Rashid et al, 2007a;So et al, 2009;Verma et al, 2010) and the expression of dopamine D1-D2 receptor heteromers in the mesocorticolimbic system and basal ganglia nuclei suggest this receptor complex may have etiological significance in disorders characterized by abnormal dopamine signaling. More specifically, calcium signaling elicited by the D1-D2 heteromer, through activation of Gq/11 and phospholipase C (PLC), resulted in the activation of calcium calmodulin kinase IIa (CaMKII) (Ng et al, 2010;Perreault et al, 2012;Rashid et al, 2007a) and consequently increased expression of brain-derived neurotrophic factor (BDNF) in NAc and ventral tegmental area (VTA) (Hasbi et al, 2009;Perreault et al, 2012) (Figure 1), both of which have significant roles in the pathological processes underlying drug addiction. For instance, CaMKII in NAc shell has been shown to be critical to cocaine seeking, serving as a biochemical link between dopamine and glutamate (Anderson et al, 2008).…”
Section: The Dopamine D1-d2 Receptor Heteromermentioning
confidence: 99%
“…More recently, it has been suggested that there is a unique role of D 1 -D 2 heterodimers in subsets of coexpressing striatal neurons (Perreault et al, 2012(Perreault et al, , 2014. Although this is a change from the original hypothesis of direct D 1 -Ga Q -PLC activation by SKF-83959, it is important to consider its merits.…”
Section: Hypothesis: D 1 -D 2 Heterodimer-mediated Activation Of Ga Qmentioning
confidence: 99%